Upaya Guru PAI Dalam Meningkatkan Kemampuan Psikomotorik Siswa ABK Tunagrahita Melalui Model Contextual Teaching And Learning (CTL) - Basri, Junaidin; Muharom, Mohamad Karom (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
This study is motivated by the challenges faced by students with intellectual disabilities (Tunagrahita) in understanding and retaining educational material due to their limited cognitive abilities. Contextual Teaching and Learning (CTL) encourages students to connect their knowledge with practical applications in everyday life, thereby engaging them in meaningful activities that reinforce their understanding. This research focuses on the efforts of Islamic Religious Education (PAI) teachers to enhance the psychomotor skills of students with intellectual disabilities through the implementation of the CTL model. The objectives of this research are to describe the strategies employed by PAI teachers in improving the psychomotor abilities of intellectually disabled students by applying the CTL model. The methodology used in this study is qualitative with a descriptive approach. The subjects of the research are PAI teachers, and the objects are students with intellectual disabilities (ABK). Data collection techniques include observations, documentation, and interviews with PAI teachers and classroom teachers. The data are analyzed using the Huberman and Milles theoretical framework. The findings of the research are as follows: (1) PAI teachers at SLB Al-Masduqiah have successfully applied the principles and steps of the CTL model in classroom teaching; (2) the main challenges faced by PAI teachers include the students' cognitive limitations in receiving material, the lack of specific teaching materials and textbooks for PAI tailored to students with disabilities, and the absence of standardized evaluation systems for intellectually disabled students; (3) the impact of the CTL model on students' psychomotor skills includes increased student activity, enhanced learning motivation, and improved routine practice of Dhuha prayer, which aligns with the principles of psychomotor domain assessment. Therefore, the study recommends the implementation of the CTL model by PAI teachers in special schools. Keywords: PAI Teachers; Contextual Teaching and Learning Model; Psychomotor Skills; Students with Intellectual Disabilities